PENGARUH KOMPOS TANDAN KOSONG KELAPA SAWIT DAN PUPUK NPK TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L. ) - hasibuan, Syahrial; Saputra, Sukemi Indra; ', Nurbaiti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This study aims to determine the effectiveness of compound TKKS and NPK  fertilizerAnd get the best combinationNPKand TKKSon the growth ofcocoa seedlings(Theobroma cacao L.).This research was conducted at the experimental station Faculty of Agriculture,University of Riau in august-november 2013.Completely Randomized Designwith twoFactor use in this experiment the treatment consisted factor 1 isGivingCompostTKKSwith4 levels, namely: (K0): WithoutgivingTKKSCompound, (K1): GivingCompound TKKSdose20g /polybag, (K2): Givinga dose of40g ofcompoundTKKS/polybag, (K3): GivingCompoundTKKSdoses of 60g/polybag. FactorII: NPKfertilizerwith4 levels: (M0): WithoutNPK fertilizer, (M1): NPKdose of1g/polybag, (M2): NPKdose of2g/polybag, (M3): NPKdose3g/polybag.Data wereanalyzed using analysist of varianceand mean separation with Duncan's testNewMultiple Range Testatthe 5 % level.The Parametersmeasured were theplant height(cm), stemdiameter(mm), number of leaves(strands), leafarea(cm2). The results showed that application of Giving Compound TKKS doses of 60 g / polybag and NPK fertilizer dose of 2 g / polybag give a better effect on the parameters of plant height, stem diameter and number of leaves. GivingCompoundTKKSnotaffectsignificantly affectedall treatments. NPK fertilizerwitha dose of2g/polybagbettereffecton theparameters ofplant height, stem diameter andnumber of leaves. Keywords:Cocoa, TKKSCompound, FertilizerNPK.